The "Aegis" Framework: A Multi-Cloud, Fault-Tolerant MLOps Architecture for Real-Time Financial Decisioning and Regulatory Compliance (International Journal of Engineering & Extended Technologies Research (IJEETR), 2025)
The paper provides the findings of a quantitative study on Aegis Framework, a multi-cloud MLOps framework that is aimed at financial institutions. The results point out that the framework is much more beneficial on the availability, speed of the fail-over, and precision of governance in the scenario of working with real-time decision workloads. The cross-cloud routing did not break the inference services whenever cloud failures were detected, and Mean Time to Recovery was less than two seconds. During all stress tests, checking of governance was not lost and metadata logs were not lost. Peak loads high throughput and low latency was obtained as well. These findings confirm that Aegis offers high reliability and resilience as well as compliance performance to the modern financial systems.
Keywords: MLOps; Finance; Regulation; Multi-Cloud; Architecture; Compliance